Analysis of scattering by a large array of waveguide-fed wide-slot millimeter wave antennas using precorrected-FFT algorithm - Zhang, Min; Li, Le-Wei; Ma, An-Ying (IEEE microwave and wireless components letters, 2005)
An effective numerical technique employing the precorrected-fast Fourier transform (P-FFT) technique based on the method-of-moments (MoM) is presented to study the scattering from wide-slot antennas fed by waveguides with arbitrary terminations. As the Rao-Wilton-Glisson (RWG) functions are used as the basis and testing functions, the magnetic currents with arbitrary slot directions are considered. In addition, the P-FFT technique is employed to accelerate the MoM procedure for a large slot array. The numerical results are obtained and compared with both the traditional MoM results obtained using the entire-domain basis functions and the experiments results, to demonstrate better effectiveness and accuracy of this technique for millimeter wave scattering from arbitrary wide-slot antennas.